2020
DOI: 10.1101/2020.05.15.20103044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trialstreamer: a living, automatically updated database of clinical trial reports

Abstract: Objective Randomized controlled trials (RCTs) are the gold standard method for evaluating whether a treatment works in healthcare, but can be difficult to find and make use of. We describe the development and evaluation of a system to automatically find and categorize all new RCT reports. Materials and Methods Trialstreamer, continuously monitors PubMed and the WHO International Clinical Trials Registry Platform (ICTRP), looking for new RCTs in humans using a validated classifier. We combine machine learning a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…27 Further metrics included under 'Other' were odds ratios, 37 normalised discounted cumulative gain, 29 'sentences needed to screen per article' in order to find one relevant sentence, 38 McNemar test, 36 C-statistic (with 95% CI) and Brier score (with 95% CI). 39 Real-life evaluations, such as the percentage of outputs needing human correction, or time saved per article, were reported by one publication, 30 and an evaluation as part of a wider screening system was done in another. 40 There were several approaches and justifications of using macro-or micro-averaged precision, recall, or F1 scores in the included publications.…”
Section: Reported Performance Metrics Used For Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Further metrics included under 'Other' were odds ratios, 37 normalised discounted cumulative gain, 29 'sentences needed to screen per article' in order to find one relevant sentence, 38 McNemar test, 36 C-statistic (with 95% CI) and Brier score (with 95% CI). 39 Real-life evaluations, such as the percentage of outputs needing human correction, or time saved per article, were reported by one publication, 30 and an evaluation as part of a wider screening system was done in another. 40 There were several approaches and justifications of using macro-or micro-averaged precision, recall, or F1 scores in the included publications.…”
Section: Reported Performance Metrics Used For Evaluationmentioning
confidence: 99%
“…One, for example, applied their system to new, unlabelled data and reported that classifying the whole of PubMed takes around 20 hours using a graphics processing unit (GPU). 39 In another example, the authors reported using Google Colab GPUs, along with estimates of computing time for different training settings. 68 3.4.2.4 Is the source code available?…”
Section: Is There a Description Of The Hardware Used?mentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a machine learning system which maintains a live database of annotated RCT reports, named Trialstreamer. We have described the computational methods and accuracy of the system components in detail elsewhere, 11 and summarise the key points relevant to the current study below.…”
Section: Methodsmentioning
confidence: 99%
“… 14 These machine learning models are trained 1 on 280 000 abstracts manually labelled as being RCTs or not by Cochrane Crowd, ( https://crowd.cochrane.org ) a collaborative citizen science project. We do not rely on the Publication Type index alone, as we have previously found it to miss a substantial proportion of the 5–7 most recent years of articles 11 (due to delay in manual indexing after publication). We next removed any RCTs that were not conducted in humans (eg, animal or agricultural studies) using an SVM model.…”
Section: Methodsmentioning
confidence: 99%